2000
DOI: 10.1111/j.1553-2712.2000.tb00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Emergency Department‐based Screening and Brief Intervention for Alcohol Problems

Abstract: Abstract. Objectives: To adapt screening and brief intervention for alcohol problems (SBI) to a high-volume emergency department (ED) setting and evaluate its acceptability to patients. Methods: Patients at a large public-hospital ED were screened with the Alcohol Use Disorders Identification Test (AUDIT). Screen-positive drinkers (AUDIT score Ն 6) were provided brief, on-site counseling and referral as needed. Three months later, project staff blinded to baseline measures reassessed alcohol intake, alcohol-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 26 publications
1
38
0
2
Order By: Relevance
“…Therefore, the patient's volition to re-attend to see the AHW fades too. This problem has not been delineated before, nor highlighted as a focus of future research in the USA (Hungerford et al, 2000;D'Onofrio & Degutis LC, 2002;Hungerford & Pollok, 2003) or in mainland Europe (Daeppen J-B, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the patient's volition to re-attend to see the AHW fades too. This problem has not been delineated before, nor highlighted as a focus of future research in the USA (Hungerford et al, 2000;D'Onofrio & Degutis LC, 2002;Hungerford & Pollok, 2003) or in mainland Europe (Daeppen J-B, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…There are considerable data to support ED-based patient education projects. 17 This issue of AEM also contains an article by Hungerford et al, 18 in which a screening tool to identify problems related to alcohol use was studied, and a brief ED-based intervention was applied. The short-term outcome of the ED intervention was assessed at three months, to determine the status of those patients who screened positive for alcohol-related problems and who accepted the ED intervention.…”
mentioning
confidence: 99%
“…In other US studies involving direct patient interviews, researchers found evidence of alcohol problems in 54% of drinking college students presenting to ED, 7 in 43% of young adult drinkers 8 and in 21% of all adult ED patients. 9 In a British study, Thom and coworkers 10 found that 37% of young adults attending the accident and emergency department were drinking harmfully, and 15% considered their visit to be alcohol related. Cherpitel and colleagues 18 interviewed patients in 2 Canadian EDs and found that 22% of injured patients and 11% of noninjured patients in 2 Canadian EDs reported using alcohol in the 6 hours before their visit, and that 3% of injured patients and 2% of noninjured patients reported drug use in the previous 6 hours.…”
Section: Discussionmentioning
confidence: 99%
“…4 Numerous studies document a prevalence of substance abuse or dependence in approximately 20% of ED patients. [5][6][7][8][9][10][11][12] Substance abuse has been associated with up to 50% of all injuries. [13][14][15][16][17] Although the bulk of these data is from the United States, the Canadian situation is likely similar.…”
Section: Introductionmentioning
confidence: 99%